Bonsoir
Dans chaque cas, calculer sous forme fractionnaire en détaillant les étapes. Simplifier le résultat, si possible.
1)
[tex]A = ( \frac { 3 } { 15 } - \frac { 8 } { 5 } ) \times \frac { 5 } { 4 }[/tex]
[tex]A=\left(\frac{1}{5}-\frac{8}{5}\right)\times \left(\frac{5}{4}\right) [/tex]
[tex]A=\frac{1-8}{5}\times \left(\frac{5}{4}\right) [/tex]
[tex]A=-\frac{7}{5}\times \left(\frac{5}{4}\right) [/tex]
[tex]A=\frac{-7\times 5}{5\times 4} [/tex]
[tex]A=\frac{-7}{4} [/tex]
[tex]A=-\frac{7}{4} [/tex]
2)
[tex]B = \frac { - 2 } { 24 } + \frac { - 6 } { 8 } \times \frac { - 9 } { 3 }[/tex]
[tex]B=-\frac{1}{12}+\frac{-6}{8}\times \left(\frac{-9}{3}\right) [/tex]
[tex]B=-\frac{1}{12}-\frac{3}{4}\times \left(\frac{-9}{3}\right) [/tex]
[tex]B=-\frac{1}{12}-\frac{3}{4}\left(-3\right) [/tex]
[tex]B=-\frac{1}{12}+\frac{-3\left(-3\right)}{4} [/tex]
[tex]B=-\frac{1}{12}+\frac{9}{4} [/tex]
[tex]B=-\frac{1}{12}+\frac{27}{12} [/tex]
[tex]B=\frac{-1+27}{12} [/tex]
[tex]B=\frac{26}{12} [/tex]
[tex]B=\frac{13}{6} [/tex]
3)
[tex]c = \frac { 5 } { 21 } - \frac { 3 } { 7 } \times \frac { 5 } { 3 } + \frac { 3 } { 7 }[/tex]
[tex]c=\frac{5}{21}-\frac{3\times 5}{7\times 3}+\frac{3}{7} [/tex]
[tex]c=\frac{5}{21}-\frac{5}{7}+\frac{3}{7} [/tex]
[tex]c=\frac{5}{21}-\frac{15}{21}+\frac{3}{7} [/tex]
[tex]c=\frac{5-15}{21}+\frac{3}{7} [/tex]
[tex]c=-\frac{10}{21}+\frac{3}{7} [/tex]
[tex]c=-\frac{10}{21}+\frac{9}{21} [/tex]
[tex]c=\frac{-10+9}{21} [/tex]
[tex]c=-\frac{1}{21} [/tex]